2006
DOI: 10.1212/01.wnl.0000216273.94142.84
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lamotrigine on cognition in children with epilepsy

Abstract: Lamotrigine exhibits no clinically significant cognitive effects in adjunctive therapy for children with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 31 publications
1
32
1
5
Order By: Relevance
“…One double-blind, placebo-controlled crossover study of 81 patients with refractory partial seizures demonstrated no adverse effect on cognition in association with lamotrigine [Smith et al 1993], and other studies have reported similar findings [Bootsma et al 2008b;Gillham et al 2000;Aldenkamp et al 1997]. For example, in a double-blind, placebocontrolled study involving children, there were no differences in the results of cognitive tasks assessing reaction time, recognition memory, attention, visual search and working memory [Pressler et al 2006]. Positive effects on cognitive function in epilepsy have also been reported [Placidi et al 2000;Banks and Beran, 1991].…”
Section: Pregabalinmentioning
confidence: 79%
“…One double-blind, placebo-controlled crossover study of 81 patients with refractory partial seizures demonstrated no adverse effect on cognition in association with lamotrigine [Smith et al 1993], and other studies have reported similar findings [Bootsma et al 2008b;Gillham et al 2000;Aldenkamp et al 1997]. For example, in a double-blind, placebocontrolled study involving children, there were no differences in the results of cognitive tasks assessing reaction time, recognition memory, attention, visual search and working memory [Pressler et al 2006]. Positive effects on cognitive function in epilepsy have also been reported [Placidi et al 2000;Banks and Beran, 1991].…”
Section: Pregabalinmentioning
confidence: 79%
“…The study, while showing improvement in declarative memory, does not prove that the memory improvement was related to an interaction with the corticosteroids. In patients with seizures, lamotrigine appears to have a more benign effect on cognition than some other antiseizure medications (Pressler et al, 2006). In healthy controls (Aldenkamp et al, 2002) and in animal models (Shannon and Love, 2004) lamotrigine appears to be associated with no significant changes in cognitive performance.…”
Section: Discussionmentioning
confidence: 97%
“…In children, no significant differences were present for lamotrigine compared to placebo on a computerized battery of cognitive tests (Pressler et al 2006). In the recent VA Cooperative study of elderly patients with new onset epilepsy, lamotrigine was the best tolerated, followed by gabapentin and then carbamazepine, although no formal neuropsychological data was reported (Rowan et al 2005).…”
Section: Lamotrigine (Lamictal)mentioning
confidence: 96%